Pembayaran Cashless dengan Sistem QR Code dan Perceived Trust terhadap Kepuasan Pengguna Shopeepay - Nurhayati Megayani; Abadi Sanosra; Tatit Diansari Reskiputri (BUDGETING : Journal of Business, Management and Accounting, 2021)
This study aims to determine the effect of Cashless payments with the QR Code system, and Percieved Trust on Shopeepay user satisfaction, cashless payments with the QR Code system have a positive and significant effect on user satisfaction, Percieved Trust has a positive and significant effect on user satisfaction. This research method is descriptive qualitative. The data used are secondary and primary data. Survey collection method and questionnaire instrument with Likert scale. The data analysis technique used descriptive analysis, namely multiple linear regression statistical tests using SPSS version 24. The results of the study showed that the cashless payment variable with a Sig value of 0.000 <0.05 and the Percieved Trust variable with a Sig value of 0.000 <0.05. Conclusions, namely a) if it is better and easier to transact using a cashless or cashless payment system, customer satisfaction will increase; b) if more and more trust is felt, then customer satisfaction will increase. Keywords: Shopeepay User Satisfaction, Cashless Payment, Percieved Trust, Roxy Square Jember